COOPERATION OF THE BRICS COUNTRIES IN COMBATINGDRUG CRIME - NIGMATULLIN Rishat Vakhidovich (Правовое государство: теория и практика)
At the current stage of human development, drug crime remains a global threat. Its transnational nature requires the improvement of relevant national mechanisms and the adoption of normative and legal acts aimed at countering drug crime, as well as constant interstate cooperation in this area. The evolution of the BRICS interstate union opens up new opportunities in the fight against illicit trafficking in narcotic drugs and psychotropic substances. The purpose of the article is to analyse the international legal framework of cooperation between the BRICS countries in combating drug crime, to identify the specifics of the BRICS union, to substantiate the synergistic effect of the BRICS member states’ participation in regional international anticrime organisations, and to study the practice of the BRICS Anti-Drug Working Group. Methods: the study is carried out using the dialectical method, as well as general scientific (logical, analysis, synthesis) and specific scientific methods (comparative-legal, statistical, interpretation of legal norms). Results: the article concludes that a unified international legal framework of cooperation between the BRICS member states, related organisational and legal mechanisms of international organisations of which they are members, will provide a synergistic effect and achieve tangible results in combating illicit trafficking in narcotic drugs and psychotropic substances; the activities of the BRICS Anti-Drug Working Group are systematic and aimed at consolidating the efforts of all law enforcement agencies of the member states in combating drug crime.